Revisiting the Core Ideas of Arbitration through Functional and Practical Measures - Shrestha, Anil Kumar (Kathmandu School of Law Review, 2024)
Arbitration has been vital to dispute resolution in today’s commercial society. It has been discussed, presented, and conceived as one of the prominent methods of alternative dispute settlement mechanisms. It has been said to have significant advantages over litigation in court, such as speedy process, lower cost, flexibility, confidentiality, and fair, final, and enforceable awards. However, these advantages or core ideas of arbitration must be revisited to ensure and endure the concept of arbitration itself. This paper tries to oversee the core ideas of arbitration through functional and practical measures, and the author has revisited the fundamental advantages of arbitration, such as its speed, cost, and non-litigious nature, besides debunking whether arbitration is an alternative dispute resolution mechanism.